Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let's say I have expression with multiplication which has variable x $$\int x^2e^{x^3}dx$$ So in example it shows

$$\int x^2e^{x^3}dx=\frac{1}{3}\int e^u du=\frac{1}{3}e^u+C=\frac{e^{x^3}}{3}+C$$ $u=x^3$ $du=3x^2 dx$

So I don't understand from where comes $\frac{1}{3}$ before integral and from where comes 3 in $du=3x^2 dx$

share|cite|improve this question
See this question – Américo Tavares Jul 19 '11 at 22:28
It was asked the same integral and the same substitution. – Américo Tavares Jul 19 '11 at 22:30
Indeed, the possible duplicate (…) – mixedmath Jul 20 '11 at 1:56
up vote 8 down vote accepted

This is called substitution. Here are the steps in detail:

You want to make two replacements: $u=x^3$ and $du=3x^2 dx$. But you don't have $3x^2 dx$ in your integral. No matter, construct it! Starting with what you have:

$$\int x^2e^{x^3}dx $$

multiply by 1=3/3:

$$= \frac{3}{3}\int x^2e^{x^3}dx $$

move the 3 inside of the integral and move $x^2$ next to the $dx$:

$$= \frac{1}{3}\int e^{x^3}3x^2dx$$

Then make two replacements: $u=x^3$ and $du=3x^2 dx$.

$$ =\frac{1}{3}\int e^u du$$

These replacements are compatible with each other because if you differentiate $u=x^3$ you get $du=3x^2 dx$. In general, if what you are looking to substitute ($3x^2 dx$ in this case) differs only by a constant from what you have ($x^2 dx$) , you can introduce the constant you need by putting 1 over that constant "outside" the integral.

Your best bet is to do another very similar example right away so that this concept will solidify for you. Best!

share|cite|improve this answer

Substituting, you have $$ \int x^2e^{x^3}dx=\int x^2e^{u}\frac{du}{3x^2}=\frac{1}{3}\int e^u du $$ after canceling the $x^2$. The $3$ in $du=3x^2 dx$ comes from the fact that the derivative of $x^3$ is $3x^2$ by the power rule.

share|cite|improve this answer

We set $u=x^3$. Then, what is $\frac{d}{dx}x^3$? It is $3x^2$. That is why $du=3x^2 dx$.

share|cite|improve this answer

If you have some integral of the form $$\int x^{n-1} e^{x^n} \ dx$$ the best thing to do is to put $t = x^{n}$. What then happens is $dt =nx^{n-1} dx$. Now you have $x^{n-1}\cdot dx$ inside the integral and you want to express everything in terms of $t$. You see that $\frac{dt}{n} = x^{n-1} \ dx$. So put this inside and your integral becomes $$\int e^{t} \cdot \frac{1}{n} \cdot dt$$ which is precisely what you have done for the case $n=3$.

share|cite|improve this answer

The substitutions are made to simplify things. I think that you should understand why it works.

If $F$ is primitive of $f$ (i.e. $F'(x)=f(x)$) and $g$ is a function such that $f(g(x))$ and $F(g(x))$, both, makes sense, then the function $$f(g(x))g'(x)$$ has a primitive, namely $F(g(x))$. This follows by the chain rule.

In your case $$f(t)= e^t,\qquad F(t)=e^t,\qquad\text{and}\qquad g(x)=x^3,$$ thus $$f(g(x))=e^{x^3}$$ and you want $g'(x)f(g(x))$. Now, $$g'(x)=3x^2$$ and you already have $x^2$, so you must produce $3x^2$ in some way. In this case it is easy because $$\begin{align*} \int x^2e^{x^3}dx &=\int 1\cdot x^2e^{x^3}dx\\ &=\int\frac{1}{3}\cdot 3x^2e^{x^3}dx\\ &=\frac{1}{3}\int 3x^2e^{x^3}dx=\frac{1}{3}\int g'(x)f(g(x))dx\\ &=\frac{1}{3}F(g(x))\\ &=\frac{1}{3}e^{x^3}. \end{align*}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.